Epidermal Growth Factor Receptor Gene in Non-Small-Cell Lung Cancer: The Importance of Promoter Polymorphism Investigation - Vladimir Jurišić; Jasmina Obradovic; Sonja Pavlović; Nataša Djordjevic (Analytical Cellular Pathology)
Recently, epidermal growth factor receptor (EGFR) was a key molecule in investigation of lung cancer, and it was a target for a new therapeutic strategy, based on molecular analyses. In this review, we have summarized some issues considering the role of EGFR in lung cancer, its coding gene, and its promoter gene polymorphisms (SNPs) -216G/T and -191C/A in non-small-cell lung cancer (NSCLC). The position of the SNPs indicates their significant role in EGFR regulation. The accumulation of knowledge regarding SNPs lately suggests their significant and important role in the onset of carcinogenesis, the prediction of the onset of metastases, the response to therapy with TKI inhibitors, and the onset of toxic effects of the applied therapy. Based on this, we suggest further studies of the relationship of clinical significance to SNPs in patients with lung tumors.